Influence of male targeted short message service on knowledge, nature of attitude and male involvement on uptake of family planning among spouses in Marsabit County, Kenya - Matoke, Vincent O.; Gitonga, Eliphas M.; Owaka, Isaac O.; Okari, Geoffrey M.; Mutabazi, Michel; Ogutu, Gideon M.; Odhiambo, Felix B.; Anyika, Daniel K.; Salima, Ruth; Okenyoru, Douglas S. (International Journal Of Community Medicine And Public Health, 2024)
Background: Family planning services helps the individuals or couples to regulate the number and determine healthy spacing and timing of pregnancies. Globally, contraceptive prevalence stands at 49.0%, Sub-Saharan Africa at 29.0%, Kenya at 56.9% and Marsabit County at 5.6%. Some of the reasons given for low uptake include low knowledge level, negative attitude and lack of male involvement on family planning matters. This study aimed at establishing the influence of male targeted short message service on knowledge, nature of attitude and male involvement on uptake of family planning among spouses in Marsabit County. Methods: A pre-test and post-test quasi experimental study design was adopted involving randomly selected 220 couples from Laisamis (control group) and Moyale (intervention group) sub-counties. Intervention of male targeted short message service was offered weekly to male spouses from Moyale sub-county. A questionnaire was used to collect data. Data analysis was done using SPSS. All the required ethical and logistical considerations were adhered to accordingly. Results: Male targeted short message service increased level of knowledge significantly (OR 4.173, p=0.001), changed nature of attitude (OR 2.7335, p=0.004) and male involvement in family planning (OR 4.4306, p=0.001). Conclusions: The study concluded male targeted SMS intervention increased level of knowledge, attitude changed and males were involved. The County government of Marsabit should engage opinion leaders in family planning to help in educating and changing the attitude of the men towards family planning.